Real‐life experience with the combination of polatuzumab vedotin, rituximab, and bendamustine in aggressive B‐cell lymphomas. Issue 3 (2nd March 2021) - Dimou, Maria; Papageorgiou, Sotirios G.; Stavroyianni, Niki; Katodritou, Eirini; Tsirogianni, Maria; Kalpadakis, Christina; Banti, Anastasia; Arapaki, Maria; Iliakis, Theodoros; Bouzani, Maria; Verrou, Eugenia; Spanoudakis, Emmanouil; et al.
Abstract: Transplant‐ineligible relapsed/refractory (rr) diffuse large B‐cell lymphoma (DLBCL) patients represent an unmet medical need. Polatuzumab vedotin (Pola), an anti‐CD79b antibody‐drug‐conjugate (ADG), with bendamustine‐ rituximab(BR) has recently gained approval for these patients, both in the USA and Europe, based on the GO29365 phase IIb trial. Real‐life data with Pola are extremely limited. We report the outcomes of 61 Greek patients, who received Pola‐(B)R mainly within a compassionate use program. Treatment was given for up to six 21‐day cycles. Bendamustine was omitted in three cases due to previous short‐lived responses. Fourty‐nine rrDLBCL(efficacy cohort‐EC) and 58 rr aggressive B‐NHL (safety cohort‐SC) patients received at least 1 Pola‐BR cycle. Twenty‐one (43%) patients of the EC responded with 12/49 (25%) CR and 9/49 (18%) PR as best response. Median progression–free survival, overall survival and duration of response were 4.0, 8.5, and 8.5 months respectively, while 55% of patients experienced a grade ≥3 adverse event, mainly hematologic. Treatment discontinuations and death during treatment were mainly due to disease progression. Twenty‐two (41%) patients received further treatment; 11/22 are still alive, including one after CAR‐T cells, and two after stem cell transplantation. Our data confirm that Pola‐BR is a promising treatment for rrDLBCL patients, inducing an adequate response rate with acceptable toxicity. Pola‐BR could be used as bridging therapy before further consolidative treatments.